Evaluating gender gaps in STEM achievement in African secondary schools: a quantile regression and mediation analysis approach - Bulala, Tapela; Ntumi, Simon (Frontiers in Education, 2025)
IntroductionDespite global efforts to close gender gaps in education, persistent disparities in STEM achievement remain a critical challenge in many African secondary schools, Q9 warranting rigorous empirical investigation. This study investigated gender disparities in STEM achievement among secondary school students in Africa using quantile regression and mediation analysis.MethodsThe study adopted a quantitative, cross-sectional research design to examine the nature, extent, and underlying factors contributing to gender disparities in STEM achievement across selected African countries. Data were drawn from two large-scale and methodologically robust international education assessments SACMEQ IV and PASEC 2019 which employed multi- stage stratified sampling procedures. The final analytical sample included several thousand Grade 6 and 8 students from public and private schools, representing diverse socioeconomic and geographic contexts across the continent.Results and discussionResults show a significant gender gap at lower performance levels: at the 10th percentile, female students scored 2.53 points lower than males (p = 0.028), and at the 25th percentile, the gap was 1.92 points (p = 0.027). The gap narrowed and became statistically non-significant at the 75th and 90th percentiles. Effect size estimates (Cohen’s d = −0.31 at 10th percentile) confirm the pronounced disadvantage for low-performing female students. Mediation analysis revealed that self-efficacy accounted for 39.7% of the gender effect on STEM achievement, with female students reporting lower mean self-efficacy (3.45 vs. 3.62). Other significant mediators included parental involvement (31.3%), anxiety (19.7%), and home learning resources (27.0%). Moderated mediation and interaction effects showed that gender disparities were larger in rural areas (−3.12, p = 0.031), among low-SES students (−5.22, p = 0.019), and in public schools (−4.18, p = 0.021). Significant gender × context interactions were also found for parental education and digital access. Hierarchical regression models explained 39.6% of the variance in STEM scores, with good model fit (SRMR = 0.038; RMSEA = 0.036). The findings emphasize the combined influence of psychological factors and contextual inequalities in shaping gender gaps. Recommendations include gender-sensitive curricula, self-efficacy programs, parental engagement, and resource investment in underserved schools to foster equitable STEM outcomes across Africa.